SYNERGISTIC EFFECTS OF VIRTUAL REALITY-BASED REHABILITATION AND PHARMACOLOGICAL MANAGEMENT ON PAIN AND FUNCTION IN PATIENTS WITH KNEE OSTEOARTHRITIS: A NOVEL INTEGRATIVE APPROACH - Vaheedha S , Vinodh Kumar Rama Lingam , Neeha Tabita Guzari , K. Vinitha , Sandhya Kiran Mullangi , Ramya Krishna M.L. (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Background: A common degenerative joint disease, knee osteoarthritis (OA) is marked by persistent discomfort, decreased mobility, and a lower quality of life. Traditional pharmacological treatment, such as the use of analgesics and non-steroidal anti-inflammatory medications (NSAIDs), relieves symptoms but ignores functional restrictions. A promising supplementary therapy for increasing physical activity and encouraging neuromuscular engagement in a safe, stimulating setting is virtual reality (VR)-based rehabilitation. Objective: The purpose of this study is to evaluate the way pharmaceutical treatment and virtual reality-based rehabilitation work together to improve knee OA patients' functional abilities and reduce pain. Methods: Thirty people with grade 2 and grade 3 osteoarthritis of the knee were divided into two groups at random, with 15 participants each: Group A received pharmaceutical management, while Group B received pharmaceutical management combined with VR-based rehabilitation sessions. Low-Level Laser Therapy was also administered to both groups as a component of standard physical therapy. The Numerical Pain Rating Scale (NPRS) for pain, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and range-of-motion evaluations will be used as outcome measures both before and after the intervention. Outcome Measures: WOMAC Questionnarie and NPRS Results The Numerical Pain Rating Scale (NPRS) scores indicated that both Group A (pharmacological management alone) and Group B (pharmacological management combined with virtual reality-based rehabilitation) were effective in reducing pain. However, Group B demonstrated greater improvement in pain reduction compared to Group A. In terms of functional improvement, assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and range of motion (ROM), Group B showed statistically significant improvement (p < 0.05) over Group A. Participants in Group B achieved faster gains in joint mobility and greater functional independence, indicating the added benefit of incorporating virtual reality-based rehabilitation alongside pharmacological treatment. These findings suggest that while both interventions were effective, the combination approach in Group B was more effective than Group A in improving both pain and functional outcomes, supporting the efficacy of a synergistic rehabilitation strategy for managing knee osteoarthritis. Conclusion: The combination of virtual reality-based rehabilitation with pharmacological management was more effective than pharmacological treatment alone in improving pain and functional outcomes in patients with knee osteoarthritis. This integrative approach enhances mobility and supports faster functional recovery.